An antibacterial and fresh-keeping composite gel film based on portulaca oleracea-derived carbon dots and a preparation method and application thereof
Patent Information
- Application Number
- CN202611303676.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-08-26
- Publication Date
- 2026-10-27
AI Technical Summary
[0006]本发明针对上述现有食品保鲜薄膜中抗菌组分稳定性差、无机纳米抗菌剂存在潜在迁移风险、薄膜在高湿环境下易失水或溶胀、综合保鲜功能不足等问题,提供了一种基于马齿苋衍生碳点的抗菌保鲜复合凝胶薄膜及其制备方法与应用
(1)本发明以药食同源中药材马齿苋为碳源制备R-CDs,原料绿色安全、来源广泛,适合食品接触材料应用。马齿苋本身具有清热解毒、抑菌消炎等功效,以其为碳源制备的碳点具有良好的生物安全性和抗菌活性。
Smart Images

Figure CN122978629A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of food packaging and preservation materials technology, specifically to an antibacterial and preservation composite gel film based on purslane-derived carbon dots, its preparation method, and its application. Background Technology
[0002] Currently, antibacterial preservation films are mainly prepared using natural or biodegradable polymers such as chitosan, sodium alginate, gelatin, starch, cellulose, polyvinyl alcohol, and polylactic acid as the matrix through blending, coating, cross-linking, and casting. To endow the film with active preservation functions, plant essential oils, tea polyphenols, organic acids, flavonoids, antimicrobial peptides, lysozyme, nisin, and inorganic nano-antimicrobial agents such as silver, zinc oxide, and titanium dioxide are often introduced. These films can form a protective layer on the surface of food, reducing moisture loss, blocking oxygen, and inhibiting the growth of bacteria and mold, thereby delaying the spoilage of meat, aquatic products, fruits, and vegetables. In recent years, composite materials, nano-reinforcement, slow-release antibacterial properties, and biodegradable packaging have become important development directions for antibacterial preservation films.
[0003] While existing antibacterial preservation films offer some preservation benefits, they still have several shortcomings. First, some natural antibacterial components, such as plant essential oils and polyphenols, are volatile, easily oxidized, or degraded by light and heat, leading to unstable and short-lasting antibacterial effects. Second, although inorganic nano-antibacterial agents have strong antibacterial capabilities, they suffer from particle aggregation, uneven dispersion, and potential migration risks, posing a concern for food contact safety. Third, some films lack sufficient water resistance, mechanical strength, and flexibility, making them prone to swelling, rupture, or loss of barrier properties in high-humidity food environments. Furthermore, many films have limited functions, providing only basic antibacterial or physical barrier effects, failing to simultaneously meet the comprehensive preservation needs of antibacterial, moisturizing, antioxidant, barrier, and safe degradation prevention.
[0004] The aforementioned problems primarily stem from the mismatch in compatibility, stability, and mechanism of action between the antibacterial components and the film matrix. Natural active substances are mostly small molecules or volatile components with weak binding to the polymer matrix, making them prone to rapid release, volatilization, or degradation during storage, leading to a decrease in antibacterial activity. Inorganic nanoparticles have high surface energy, easily aggregating in the film-forming system, resulting in uneven distribution, reduced effective contact area, and potentially affecting film transparency and mechanical properties. Furthermore, natural polymer films typically contain numerous hydrophilic groups, exhibiting strong hygroscopicity, and are prone to swelling and structural loosening when exposed to high-moisture foods such as meat and seafood. Simultaneously, insufficient antibacterial agent dosage is insufficient to achieve effectiveness, while excessive dosage can damage the film structure or pose safety hazards; therefore, existing technologies struggle to achieve a performance balance.
[0005] Therefore, there is an urgent need to develop a food preservation film material that combines good antibacterial properties, stability, and safety. Summary of the Invention
[0006] This invention addresses the problems of poor stability of antibacterial components in existing food preservation films, potential migration risks of inorganic nano-antibacterial agents, easy water loss or swelling of films under high humidity environments, and insufficient comprehensive preservation functions. It provides an antibacterial and preservation composite gel film based on purslane-derived carbon dots, its preparation method, and applications. This invention prepares R-CDs using purslane, a medicinal and edible herb, as a biomass carbon source and incorporates them into an acrylamide / polyvinyl alcohol (AM / PVA) gel film to construct an antibacterial and preservation composite gel film. This method combines the antibacterial, UV-shielding, and functional activities of herb-derived CDs with the film-forming properties, flexibility, water retention, and moisture barrier properties of AM / PVA gel films, achieving synergistic inhibition of spoilage factors such as water loss, oxidative discoloration, pH increase, and microbial proliferation during the refrigeration of meat products.
[0007] To achieve the above objectives, the technical solution adopted by the present invention is as follows: This invention provides a method for preparing an antibacterial and preservative composite gel film based on purslane-derived carbon dots, such as... Figure 8 As shown, the specific steps include the following: S1: Using purslane as a carbon source and pyromellitic acid as an auxiliary precursor, a red fluorescent carbon dot R-CDs solution with dual emission characteristics was synthesized by a solvothermal method. Its fluorescence emission peaks were located at 484 nm and 672 nm. S2: The R-CDs solution obtained in step S1 is mixed with polyvinyl alcohol aqueous solution and acrylamide, and a crosslinking agent and initiator are added. The mixture is then subjected to thermally initiated free radical polymerization to obtain an antibacterial and preservative composite gel film based on purslane-derived carbon dots (AM / PVA / R-CDs composite gel film).
[0008] Further, in step S1, the synthesis of the R-CDs solution specifically includes: S11: Place fresh purslane in an electric heating drying oven and dry it at 60°C until all moisture is removed, then grind it into a uniform powder; S12: Disperse the powder in anhydrous ethanol, extract at room temperature for 15 min, then filter and collect the extract; S13: Add pyromellitic acid to the extract under vigorous stirring until completely dissolved to form a precursor solution; S14: The precursor solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene and heated at 160°C for 5 hours. After naturally cooling to room temperature, the resulting suspension is centrifuged at 8000×g for 15 minutes to remove large insoluble particles. Finally, the supernatant is filtered through a 0.22μm microporous membrane to obtain the R-CDs solution.
[0009] Furthermore, the ratio of purslane powder, anhydrous ethanol, and pyromellitic acid is 1.00g:30.00mL:0.32g.
[0010] Further, in step S2, the thermally initiated free radical polymerization specifically includes: S21: Prepare a 10wt% polyvinyl alcohol (PVA) aqueous solution; S22: Add R-CDs solution at the optimal dilution ratio to the polyvinyl alcohol (PVA) aqueous solution under continuous stirring to ensure uniform dispersion; then add acrylamide (AM) and stir until completely dissolved; next, add N,N'-methylenebisacrylamide (MBA) as a crosslinking agent and potassium persulfate (KPS) solution as an initiator in sequence, and stir to obtain a uniform precursor solution; S23: Pour the precursor solution into a custom mold, seal it, and place it in an electric heating drying oven at 60°C for 2 hours to obtain an antibacterial and preservative composite gel film based on purslane-derived carbon dots (AM / PVA / R-CDs composite gel film).
[0011] Furthermore, in step S22, the optimal dilution factor of the R-CDs solution is 40 times; the volume ratio of the polyvinyl alcohol (PVA) aqueous solution, the R-CDs solution at the optimal dilution factor, acrylamide (AM), N,N'-methylenebisacrylamide (MBA), and potassium persulfate (KPS) solution is 10 mL: 5 mL: 2.0 g: 0.02 g: 1 mL; and the concentration of the potassium persulfate (KPS) solution is 0.1 M.
[0012] Furthermore, in step S22, the optimal dilution factor for the R-CDs solution is determined as follows: After centrifugation and filtration, the R-CDs solution prepared in step S1 is diluted with anhydrous ethanol to different factors. The fluorescence emission spectrum is measured using 365 nm as the excitation wavelength. The optimal dilution factor is determined based on high fluorescence intensity, stable emission peak shape, and F... 484 / F 672 The optimal dilution factor for the R-CDs solution was determined based on a small change in the ratio; the optimal dilution factor was 40 times.
[0013] Furthermore, the method also includes the step of coating the surface of the resulting composite gel film with a layer of glycerol.
[0014] The present invention also provides an antibacterial and preservative composite gel film based on purslane-derived carbon dots prepared by the above preparation method.
[0015] The present invention also provides an application of an antibacterial and preservative composite gel film based on purslane-derived carbon dots in food preservation.
[0016] Furthermore, the applications include using the composite gel film as a food contact antimicrobial packaging film, preservation patch, packaging liner, or functional coating to reduce food weight loss, delay pH rise, inhibit microbial growth, and maintain sensory quality; the food includes meat, aquatic products, and fruits and vegetables.
[0017] Compared with the prior art, the beneficial effects of the present invention are as follows: (1) This invention uses purslane, a Chinese medicinal herb that is both food and medicine, as a carbon source to prepare R-CDs. The raw material is green, safe, and widely available, making it suitable for food contact materials. Purslane itself has the effects of clearing heat and detoxifying, inhibiting bacteria and reducing inflammation. The carbon dots prepared using it as a carbon source have good biosafety and antibacterial activity.
[0018] (2) The R-CDs obtained by this invention have small particle size (average diameter 2.83 nm), good dispersibility, and rich oxygen / nitrogen functional groups on the surface. They can form good compatibility and hydrogen bonding with AM / PVA matrix, avoiding the problems of easy aggregation and potential migration risk of traditional inorganic nano antibacterial agents.
[0019] (3) The present invention uses AM / PVA gel film as the substrate and forms a dense three-dimensional network structure through thermally initiated free radical polymerization. A large number of hydroxyl groups in the PVA molecular chain form rich hydrogen bond interactions with the functional groups on the surface of polyacrylamide segments and R-CDs, giving the film good film-forming properties, flexibility, water retention and water vapor barrier properties, which can effectively reduce water loss, shrinkage and oxidative browning during the cold storage of meat products.
[0020] (4) In this invention, R-CDs endow the composite gel film with ultraviolet shielding and antibacterial functions, which can inhibit microbial growth and delay the pH increase during food spoilage. R-CDs have dual emission fluorescence characteristics (484nm and 672nm), and the fluorescence intensity ratio (F) at different excitation wavelengths is significantly higher. 484 / F 672 It is stable and has good ratio luminescence stability, which is beneficial for the solid-state luminescence application of composite gel films.
[0021] (5) The composite gel film of the present invention has excellent overall preservation performance. Pork preservation experiments show that the weight loss rate of the film on the 10th day is only 12.82%, which is significantly lower than that of the blank group (29.51%) and the commercial polyethylene (PE) film group (21.98%); the pH value is maintained at 5.48, which is significantly lower than that of the blank group (6.55) and the PE group (6.08); the antibacterial rate reaches 44.78%, and the overall preservation effect is better than that of the blank group and the commercial PE film.
[0022] (6) The preparation method of the present invention is simple, mild, and the raw materials are readily available, making it easy to scale up production. It has broad application prospects in the field of food preservation such as meat, aquatic products, fruits and vegetables. Attached Figure Description
[0023] Figure 1 Characterization of R-CDs and AM / PVA / R-CDs composite gel films: A: TEM image of R-CDs; B: HRTEM image of R-CDs; C: Particle size distribution of R-CDs; D: FT-IR spectrum of R-CDs; E: Cross-sectional SEM image of AM / PVA / R-CDs composite gel film (low magnification, ×5,000); F: Cross-sectional SEM image of AM / PVA / R-CDs composite gel film (medium magnification, ×30,000); G: Cross-sectional SEM image of AM / PVA / R-CDs composite gel film (high magnification, ×50,000); H: Photograph of AM / PVA / R-CDs composite gel film; I: Photographs of untreated AM / PVA gel film and AM / PVA / R-CDs composite gel film under UV light irradiation; J: Tensile demonstration of AM / PVA / R-CDs composite gel film. Figure 2 XPS characterization of R-CDs, where A: total spectrum of R-CDs; B: high-resolution C 1s spectrum of R-CDs; C: high-resolution N 1s spectrum of R-CDs; D: high-resolution O 1s spectrum of R-CDs. Figure 3 The optical properties of R-CDs are shown below, where A: UV-Vis absorption spectrum of R-CDs; B: Fluorescence emission spectra of R-CDs measured at different excitation wavelengths; C: Photographs of R-CDs under sunlight (left) and UV light (right); D: Corresponding intensity ratio (F... 484 / F 672 The curve showing how the wavelength changes with the excitation wavelength; Figure 4 The results of R-CDs working solution screening and stability evaluation are shown below. A: Fluorescence emission spectra of R-CDs solutions at different dilutions under 365 nm excitation; B: F-Emission spectra of R-CDs at different dilutions. 484 / F 672 Ratio changes; C: Fluorescence emission spectra of R-CDs solutions under different pH conditions; D: F-values of R-CDs under different pH conditions. 484 / F 67 2. Ratio changes; E: F of R-CDs under different incubation times 484 / F 672 Ratio change; F: F of R-CDs at different incubation temperatures 484 / F 672 Changes in ratio; Figure 5 Macroscopic photographs of fresh pork samples under different packaging conditions during 10 days of refrigeration at 4℃; Figure 6 For the preservation test results, A: weight loss curve of pork samples during 10 days of storage; B: pH value change curve of pork samples during 10 days of storage. Figure 7 The results of the antibacterial test are as follows: A: Photographs of bacterial colonies and inhibition zones in the blank group, gel group, and gel / R-CDs group; B: Comparison of colony counts in the blank group, gel group, and gel / R-CDs group; C: Comparison of antibacterial rates in the blank group, gel group, and gel / R-CDs group. Figure 8 A schematic diagram showing the synthesis routes of R-CDs and AM / PVA / R-CDs composite gel films and their applications in antibacterial and preservation applications. Detailed Implementation
[0024] To make the objectives and advantages of this invention clearer, the invention will be further described in detail below with reference to embodiments. It should be understood that the specific embodiments described herein are only for explaining the invention and are not intended to limit the invention.
[0025] Unless otherwise specified, the instruments, reagents, and materials used in the following embodiments are all conventional instruments, reagents, and materials already available in the prior art and can be obtained through legitimate commercial channels. Unless otherwise specified, the experimental methods and detection methods used in the following embodiments are all conventional experimental methods and detection methods already available in the prior art.
[0026] In the following embodiments, Experimental reagents: Potassium persulfate (KPS), pyromellitic acid (PMA), and polyvinyl alcohol (PVA, molecular weight approximately 67,000, degree of hydrolysis 98-99%) were purchased from Tianjin Tianli Chemical Reagent Co., Ltd. (Tianjin, China). N,N'-methylenebisacrylamide (MBA, 99.53%) and acrylamide (AM, 98%) were provided by Shanghai Bid Pharmaceutical Technology Co., Ltd. (Shanghai, China). All chemical reagents were of analytical grade and used directly without further purification. Fresh pork and purslane were purchased from a local supermarket. Ultrapure water was used in the experiments.
[0027] Experimental Equipment: The morphology and particle size distribution of R-CDs were characterized using transmission electron microscopy (TEM; Talos F200, Thermo Fisher Scientific, Hillsborough, Oregon, USA). Surface functional groups were analyzed using Fourier transform infrared spectroscopy (FT-IR; Nicolet iS5, Thermo Fisher Scientific, Waltham, Massachusetts, USA), while elemental composition and chemical state were detected using X-ray photoelectron spectroscopy (XPS; K-Alpha, Thermo Fisher Scientific, East Grinstead, UK). The UV-Vis absorption spectra of R-CDs were recorded using a UV-Vis spectrophotometer (UV-vis; UV2300 II, Tianmei, Shanghai, China), and their fluorescence spectra were obtained using a fluorescence spectrophotometer (FL; F97Pro, Prism Technology, Shanghai, China). The microstructure of the AM / PVA / R-CDs composite gel film was observed using scanning electron microscopy (SEM; JSM-7610FPlus, JEOL, Tokyo, Japan).
[0028] Example 1 Synthesis of R-CDs 1. Synthesis of R-CDs S11: Place fresh purslane in an electric heating drying oven and dry it at 60°C until all moisture is removed, then grind it into a uniform powder; S12: Disperse 1.00g of the powder in 30.00mL of 99% anhydrous ethanol, extract at room temperature for 15min, then filter and collect the extract; S13: Add 0.32g of pyromellitic acid to the extract under vigorous stirring until completely dissolved to form a precursor solution; S14: Transfer the precursor solution to a stainless steel autoclave lined with polytetrafluoroethylene and heat at 160°C for 5 hours; after naturally cooling to room temperature, centrifuge the resulting suspension at 8000×g for 15 minutes to remove large insoluble particles; finally, filter the supernatant through a 0.22μm microporous membrane to obtain the R-CDs solution (stored at 4°C).
[0029] 2. Characterization of R-CDs TEM characterization ( Figure 1 A) shows that R-CDs are quasi-spherical, well-dispersed, and show no obvious aggregation. Particle size distribution statistical analysis ( Figure 1 (C) indicates that its particle size distribution ranges from 1.48 to 4.85 nm, with an average diameter of 2.83 nm, consistent with typical characteristics of CDs. Furthermore, HRTEM images ( Figure 1B) Clearly discernible lattice fringes are observed, with an interplanar spacing of 0.26 nm. This spacing closely matches the crystal planes of graphitic carbon, indicating that purslane and the PMA precursor formed crystalline graphitic carbon nuclei during the solvothermal process. FT-IR spectroscopy analysis shows that R-CDs are visible at 3334 cm⁻¹. -1 The presence of a broad absorption band at this point can be attributed to the OH / NH stretching vibration on the surface, indicating the abundance of hydrophilic groups such as hydroxyl and amino groups on its surface. Figure 1 D). 2982 cm -1 The absorption peak at 1732 cm⁻¹ corresponds to the CH stretching vibration. -1 The characteristic peak at 1648 cm⁻¹ is attributed to the C=O stretching vibration of the carboxyl / ester group, while the peak at 1648 cm⁻¹ is attributed to the C=O stretching vibration of the carboxyl / ester group. -1 The absorption peak at that location can be attributed to sp. 2 The C=C vibrations in the carbon domain or aromatic structure confirm that R-CDs possess a certain degree of conjugated carbon skeleton. (1373, 1029, and 876 cm⁻¹) -1 The peaks at the points are attributed to CH bending vibration, CO stretching vibration, and aromatic CH out-of-plane bending vibration, respectively, further indicating that the R-CDs surface retains abundant oxygen-containing functional groups and aromatic structural features.
[0030] XPS further revealed the surface chemical environment of R-CDs. (Full spectrum) Figure 2 A) shows that R-CDs are mainly composed of C, N, and O, corresponding to C 1s (284.80 eV), N 1s (400.00 eV), and O 1s (532.00 eV), respectively. The high-resolution C 1s spectrum of the R-CDs ( Figure 2 B) can be deconvolved into three components of 284.80, 286.50, and 288.70 eV, which are assigned to CC / C=C, CO / CN, and C=O / OC=O, respectively. N 1s spectrum ( Figure 2 C) Two components are shown at 399.60 and 400.90 eV, typically attributed to pyridine / amine nitrogen (CN / C=N) and pyrrole / graphite nitrogen. O 1s spectrum ( Figure 2 D) The presence of three peaks at 531.50, 532.30, and 533.20 eV corresponds to C=O, CO / C-OH, and OC=O, respectively, indicating that the surface of R-CDs is rich in oxygen- and nitrogen-containing active sites.
[0031] 3. Optical properties of R-CDs The UV-Vis absorption spectra of R-CDs exhibit multiple characteristic absorption bands ( Figure 3 A), where the strong absorption peaks at 212.0 and 234.0 nm are attributed to the carbon nucleus sp. 2The π-π transitions of C=C bonds in the conjugated domain, and the broad shoulder peak at 287.0 nm, originate from the n-π transitions of O / N defect states on the surface, indicating that the prepared R-CDs possess significant UV absorption and a rich surface energy level structure. The corresponding fluorescence spectrum shows a distinct dual emission characteristic, with emission maxima at 484 nm and 672 nm, respectively. Regarding luminescence properties, the R-CDs aqueous solution is pale yellow and transparent under sunlight, while emitting bright pink fluorescence under 365 nm UV irradiation. Figure 3 C). To further investigate the excitation dependence of R-CDs, the excitation wavelength was varied in the range of 350–380 nm, and their fluorescence emission spectra were recorded. For example... Figure 3 As shown in Figure B, R-CDs maintain dual emission peaks at approximately 484 nm and 672 nm under different excitation wavelengths, and the peak positions do not shift significantly, indicating that their emission centers are relatively stable. Further analysis... Figure 3 D is visible, F 484 / F 672 The fluorescence intensity ratio shows minimal variation with excitation wavelength and exhibits a generally stable trend, indicating that R-CDs possess excellent ratioluminescence stability. This characteristic is beneficial for the solid-state luminescence application of R-CDs in AM / PVA gel films, enabling the composite gel film to obtain stable and uniform visible fluorescence signals without relying on a precise excitation source. In particular, 365nm is a common wavelength for portable UV lamps, which can be directly used to excite fluorescence in R-CDs / AM / PVA composite gel films, thereby improving the portability of subsequent field applications. Simultaneously, the excellent UV absorption and light conversion capabilities of R-CDs provide an optical basis for the UV shielding and photoresponsive antibacterial effects of the composite gel film.
[0032] Example 2: Screening and Stability Evaluation of R-CDs Working Solutions To screen the optimal R-CDs solution suitable for subsequent AM / PVA / R-CDs composite gel film preparation, the prepared R-CDs stock solution was centrifuged and filtered, and then diluted with anhydrous ethanol at 20, 40, 60, 80, 100, 160, and 200 times, respectively. The fluorescence emission spectra of the R-CDs solutions at different dilutions were measured using 365 nm as the excitation wavelength, and the fluorescence intensities at 484 nm and 672 nm were recorded. The optimal solution was selected based on high fluorescence intensity, stable emission peak shape, and F... 484 / F 672 Using the smallest change in ratio as a screening criterion, the R-CDs solution with the optimal dilution factor was determined as the working solution for subsequent gel preparation.
[0033] To further verify the application stability of the optimal R-CDs solution, its excitation stability, pH stability, thermal stability, and time stability were investigated. Excitation stability was evaluated by varying the excitation wavelength within the range of 350–380 nm and recording the fluorescence emission spectra. pH stability was evaluated by placing the R-CDs solution in BR buffer solutions with pH values ranging from 4.0 to 11.0 and comparing the changes in fluorescence intensity under different pH conditions. Thermal stability was evaluated by treating the R-CDs solution at 10–50 °C and then measuring its fluorescence intensity. Time stability was evaluated by placing the solution at room temperature for 0–40 min and recording the fluorescence emission intensity at regular intervals. The fluorescence intensity at 484 nm and 672 nm under different conditions and the F-wavelength difference were compared. 484 / F 672 The change in the ratio was used to determine the fluorescence stability of the R-CDs solution, providing experimental basis for its subsequent application in composite gel films.
[0034] Fluorescence spectra of R-CDs at different dilution factors under 365 nm excitation are as follows: Figure 4 As shown in Figure A, the emission intensity at 484 nm and 672 nm increases with dilution from 20-fold to 40-fold, reaching its maximum at 40-fold dilution; however, the fluorescence intensity gradually decreases with further dilution to 200-fold. This may be due to the internal filtering effect or concentration quenching at excessively high R-CD concentrations, while excessive dilution reduces the number of luminescent centers, thus leading to a decrease in fluorescence intensity. Figure 3 As can be seen from D, F under different excitation wavelengths 484 / F 672 The small change in the ratio indicates that the dual emission ratio of R-CDs is not sensitive to changes in excitation wavelength and has good excitation stability. Figure 4 B shows that F at different dilution factors 484 / F 672 The ratio remained relatively stable, indicating that changes in dilution factor did not significantly affect the dual emission ratio and luminescence stability of R-CDs. Considering both fluorescence intensity and ratio stability, a 40-fold diluted R-CDs stock solution was selected as the optimal working solution for subsequent preparation of AM / PVA / R-CDs composite gel films. The fluorescence stability of the optimal R-CDs working solution under different conditions was further investigated. Figure 4 As shown in Figure C, within the pH range of 4.0–11.0, R-CDs maintain dual emission characteristics at 484 nm and 672 nm, indicating that their dual emission structure can be maintained in different acidic and alkaline environments. Figure 4 As can be seen from D, as pH increases, F 484 / F 672 The ratio fluctuated only to a certain extent, remaining relatively stable overall, indicating that R-CDs have a certain degree of pH adaptability. The time stability results are as follows: Figure 4As shown in E, during the incubation period of 0~40 min, F 484 / F 672 The ratio remained essentially constant, indicating that the fluorescence signal of R-CDs was stable during the testing period, meeting the requirements for subsequent detection and gel preparation. The thermal stability results are as follows: Figure 4 As shown in F, within the range of 10~50℃, F 484 / F 672 The ratio showed almost no significant change, indicating that the R-CDs working solution has good tolerance to temperature changes and fluorescence stability.
[0035] Example 3 Synthesis of AM / PVA / R-CDs composite gel film 1. Synthesis of AM / PVA / R-CDs composite gel film The antibacterial and preservative composite gel film based on purslane-derived carbon dots (AM / PVA / R-CDs composite gel film) was prepared by thermally initiated free radical polymerization, as follows: S21: Prepare a 10wt% PVA aqueous solution; S22: Add 5 mL of R-CDs solution diluted 40 times to 10 mL of PVA aqueous solution under continuous stirring to ensure uniform dispersion; then add 2.0 g AM and stir until completely dissolved; next, add 0.02 g MBA and 1 mL of 0.1 M KPS solution in sequence and stir to obtain a homogeneous precursor solution; S23: Pour the precursor solution into a custom mold, seal it, and place it in an electric heating drying oven at 60°C for 2 hours to obtain an AM / PVA / R-CDs composite gel film.
[0036] The resulting AM / PVA / R-CDs composite gel film was demolded and cut into the desired shape for subsequent testing. To reduce moisture loss, a thin layer of glycerol was coated on the surface of the gel film, and then it was stored at 4°C for further experiments.
[0037] 2. Evaluation of the physical and morphological properties of AM / PVA / R-CDs composite gel films Macroscopically, the gel film appears translucent. Figure 1 H), and exhibits elasticity under sustained stretching (H), Figure 1 J). Under ultraviolet light irradiation, this composite gel film exhibits uniform yellow fluorescence compared to the original AM / PVA gel film. Figure 1 I), verifying the successful integration and uniform distribution of R-CDs. Microscopically, the cross-sectional SEM image ( Figure 1The EG structure exhibits a dense, continuous matrix with no macroscopic phase separation. Particulate features (likely representing R-CDs or localized clusters) are uniformly embedded within the polymer network. This structural uniformity indicates good compatibility between the R-CDs and the AM / PVA chains, providing a stable solid-state basis for the composite gel film.
[0038] Experiment Example 1: Preservation Test To evaluate the practical applicability of the AM / PVA / R-CDs composite gel film, pork was selected as a representative sample. Fresh pork was cut into uniformly sized cubic pieces (approximately 2.00 g each) and placed in glass vials. The samples were randomly divided into three groups: a blank group (open vials, without any wrapping), a PE group (vias sealed with commercial PE film), and a Gel / R-CDs group (vias sealed with AM / PVA / R-CDs composite gel film). All vials were stored at 4°C, and the quality deterioration of the samples was monitored from day 0 to day 10. Photographs were taken periodically to record macroscopic changes on the pork surface, with a focus on color changes, surface gloss, and mucus exudation. To evaluate the moisture barrier performance of the packaging film, the weight loss rate was calculated using the following formula: Weight loss rate (%) = (W0 - W...) / (W0 - W0 ... t ) / W0´100%, where W0 and W t The values represent the mass of the samples on the initial storage day and a specific storage day, respectively. Furthermore, following the national standard (GB 5009.237) with slight modifications, the pH value of the samples was monitored during the 10-day storage period. 0.20 g of pork sample from each treatment group was placed in a sterile mortar, 10 mL of distilled water was added, and the mixture was thoroughly ground for 2–3 min, followed by vortexing or shaking extraction for 10–15 min. The resulting homogenate was filtered through qualitative filter paper. The pH value of the filtrate was determined using a pH meter pre-calibrated with a standard buffer solution (pH 7.00). All measurements were performed in triplicate, and the results are expressed as an average.
[0039] The sensory quality of pork from different treatment groups showed significant differentiation over time. Figure 5 The unpackaged blank group, exposed to air, showed severe dehydration, volume shrinkage, and obvious oxidative browning by day 6; by day 10, it completely lost its luster and exuded mucus, exhibiting obvious signs of spoilage. The PE film group maintained its overall shape to some extent, but still showed surface whitening, edge browning, and mucus exudation in the later stages of storage (days 8-10). In contrast, the pork packaged with Gel / R-CDs maintained its fresh red color, good surface plumpness, and meat elasticity even on day 10. These macroscopic differences are directly due to moisture loss.
[0040] Quantitative weight loss curves are shown below Figure 6A. Due to the lack of a physical barrier, the blank group experienced rapid moisture evaporation, with a weight loss rate reaching 29.51% by day 10. The commercial PE film group, due to the inherent hydrophobicity of polyethylene, reduced the weight loss rate to 21.98%. Notably, the Gel / R-CDs group effectively maintained the lowest weight loss rate (12.82%), indicating that the abundant hydrogen bonding interactions and dense three-dimensional network in the AM / PVA polymer matrix endowed the composite film with excellent water vapor barrier properties, thus effectively locking in moisture from the meat. The initial pH of fresh pork is approximately 5.27 (…). Figure 6 B). After 10 days of storage, the pH values of the control group and the commercial PE film group rose to 6.55 and 6.08, respectively, indicating accelerated spoilage during storage. In contrast, the pH value of the Gel / R-CDs group only rose slightly to 5.48 on day 10, indicating that the pH increase was delayed.
[0041] Experimental Example 2: Antibacterial Test Frozen Escherichia coli was inoculated into sterile LB broth and incubated overnight at 37°C with shaking at 150 rpm. 100 μL of the bacterial culture was then thoroughly mixed with 900 μL of sterile physiological saline to prepare 10... -1 The diluent was then serially diluted 10-fold to the desired concentration. Next, 200 μL of each diluent was evenly spread onto LB agar plates using a sterile spreader. The plates were divided into three groups: a blank group (plates without any sample); a gel group (AM / PVA gel film group); and a gel / R-CDs group (a circular composite gel film placed in the center of the plate). All plates were incubated at 37°C for 24 h. After incubation, inhibition zones and colony growth were examined. Plates with colony counts between 30 and 300 CFU were selected and counted using an automated colony counter. The antibacterial rate was calculated using the following formula: Antibacterial rate (%) = (CE) / C × 100%, where C represents the average viable count of the blank group, and E represents the average viable count of the experimental groups (including the gel group and the gel / R-CDs group). All operations were performed under sterile conditions, and each experiment was independently repeated three times.
[0042] To further evaluate the antibacterial properties of the AM / PVA / R-CDs composite gel film, bacterial colony growth was observed and quantitatively analyzed. For example... Figure 7 As shown in A, 10 -5 At concentration dilutions, a large number of colonies were observed in the blank group, indicating that bacteria multiplied extensively without membrane treatment. The colony count in the gel group was moderately reduced, indicating that the pure gel membrane matrix has a certain antibacterial effect. The colony count in the gel / R-CDs group was further reduced, and at 10... -1 A clear inhibition zone appeared around the gel film at the concentration dilution, indicating that the introduction of R-CDs enhanced antibacterial activity. Quantitative analysis further confirmed this trend. Figure 7(B and 7C). The antibacterial rates of the Gel group and the Gel / R-CDs group were 21.58% and 44.78%, respectively, demonstrating that the AM / PVA / R-CDs composite gel film can effectively inhibit bacterial growth and help delay the spoilage of refrigerated pork.
[0043] In summary, from a material structure perspective, purslane contains polysaccharides, flavonoids, organic acids, amino acids, and various oxygen- and nitrogen-containing active components. During solvothermal carbonization, it can form CDs rich in surface functional groups such as hydroxyl, carboxyl, amino, and amide groups. PMA, as an auxiliary precursor, can provide aromatic conjugated structures and carboxyl sites, which is beneficial for the formation of R-CDs with graphitized carbon cores and abundant surface defect states. TEM, HRTEM, FTIR, and XPS characterization results show that the obtained R-CDs have uniform particle size, good dispersibility, graphitized carbon cores, and abundant oxygen- and nitrogen-containing active groups. These structural features not only facilitate the uniform dispersion of R-CDs in the gel film matrix but also provide a basis for their antibacterial activity and hydrogen bonding with the polymer network.
[0044] From the perspective of gel film network construction, AM forms a polyacrylamide network through thermally initiated free radical polymerization, while MBA acts as a crosslinking agent to construct a stable three-dimensional crosslinked structure. Numerous hydroxyl groups in the PVA molecular chain can form hydrogen bonds with functional groups such as hydroxyl, carboxyl, and amino groups on the surface of R-CDs. This multi-faceted interaction enables the composite gel film to form a dense and continuous network structure, improving the film's integrity, flexibility, and moisture retention capacity. SEM results show that R-CDs are uniformly distributed in the AM / PVA matrix without significant macroscopic phase separation, indicating good compatibility between R-CDs and the gel film matrix. This is crucial for maintaining the film's mechanical and functional stability.
[0045] From the perspective of preservation mechanisms, the AM / PVA / R-CDs composite gel film functions through at least the following aspects: First, the dense three-dimensional network formed by AM / PVA acts as a physical barrier, reducing surface moisture evaporation and contact with external oxygen, thus slowing down meat shrinkage and oxidative browning. Second, the abundant hydrogen bonds formed between PVA, AM, and R-CDs enhance water binding capacity, giving the gel film good moisturizing and water vapor barrier properties. Third, R-CDs possess certain UV shielding and antibacterial capabilities, reducing photo-induced oxidation and inhibiting the proliferation of microorganisms on the meat surface. Fourth, the oxygen- and nitrogen-containing functional groups and nanoscale structures on the surface of R-CDs may interact with bacterial cell membranes, disrupting cell membrane integrity or affecting bacterial metabolic processes, thereby exhibiting antibacterial effects.
[0046] The aforementioned multiple effects synergistically delay water loss, discoloration, pH increase, and bacterial proliferation in meat during refrigeration. Experimental results show that the unpackaged control group, lacking a physical barrier, experienced rapid moisture evaporation during refrigeration, resulting in significant shrinkage, browning, and mucus exudation on the meat surface. While commercial PE film can reduce moisture loss to some extent, it primarily relies on hydrophobic physical isolation and lacks active antibacterial function, thus its preservation effect is limited. In contrast, the AM / PVA / R-CDs composite gel film group maintained the pork's color, plumpness, and elasticity well even after 10 days, with a weight loss rate of only 12.82%, significantly lower than the 29.51% in the control group and 21.98% in the PE group. Simultaneously, the pH value of the pork in the Gel / R-CDs group only increased from approximately 5.27 to 5.48, significantly lower than the control and PE groups, indicating that the composite film effectively delayed protein decomposition and the accumulation of alkaline spoilage products. Further antibacterial tests showed that the number of colonies in the Gel / R-CDs group was significantly reduced and an inhibition zone appeared, with an antibacterial rate of 44.78%, which was better than that of the pure Gel group, proving that the introduction of R-CDs can enhance the antibacterial properties of the composite gel film.
[0047] Therefore, this invention does not simply involve physically mixing R-CDs with gel films. Instead, it utilizes the bioactivity, surface functional groups, and nano-dispersion properties of purslane-derived R-CDs to form a compatible, stable, and synergistic composite system with the AM / PVA crosslinking network. This system simultaneously possesses functions such as moisture retention and barrier, antibacterial and bacteriostatic properties, delaying pH rise, and maintaining the sensory quality of meat products. It can solve the problems of traditional food preservation films, such as single function, unstable active components, and short preservation period, and has good application prospects in food preservation.
[0048] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the protection scope of the present invention.
Claims
1. A method for preparing an antibacterial and preservative composite gel film based on purslane-derived carbon dots, characterized in that: Specifically, the steps include the following: S1: A solution of red fluorescent carbon dots (R-CDs) with dual emission characteristics was synthesized by solvothermal method using purslane as carbon source and pyromellitic acid as auxiliary precursor. S2: The R-CDs solution obtained in step S1 is mixed with polyvinyl alcohol aqueous solution and acrylamide, and a crosslinking agent and initiator are added. The mixture is then subjected to thermally initiated free radical polymerization to obtain an antibacterial and preservative composite gel film based on purslane-derived carbon dots.
2. The preparation method according to claim 1, characterized in that: In step S1, the synthesis of the R-CDs solution specifically includes: S11: Place fresh purslane in an electric heating drying oven and dry it at 60°C until all moisture is removed, then grind it into a uniform powder; S12: Disperse the powder in anhydrous ethanol, extract at room temperature for 15 min, then filter and collect the extract; S13: Add pyromellitic acid to the extract under vigorous stirring until completely dissolved to form a precursor solution; S14: The precursor solution is transferred to a stainless steel autoclave lined with polytetrafluoroethylene and heated at 160°C for 5 hours. After naturally cooling to room temperature, the resulting suspension is centrifuged at 8000×g for 15 minutes to remove large insoluble particles. Finally, the supernatant is filtered through a 0.22μm microporous membrane to obtain the R-CDs solution.
3. The preparation method according to claim 2, characterized in that: The ratio of purslane powder, anhydrous ethanol, and pyromellitic acid used is 1.00g:30.00mL:0.32g.
4. The preparation method according to claim 1, characterized in that: In step S2, the thermally initiated free radical polymerization specifically includes: S21: Prepare a 10wt% polyvinyl alcohol aqueous solution; S22: Add R-CDs solution at the optimal dilution ratio to the polyvinyl alcohol aqueous solution under continuous stirring to ensure uniform dispersion; then add acrylamide and stir until completely dissolved; next, add N,N'-methylenebisacrylamide as a crosslinking agent and potassium persulfate solution as an initiator in sequence, and stir to obtain a uniform precursor solution; S23: Pour the precursor solution into a custom mold, seal it, and place it in an electric heating drying oven at 60°C for 2 hours to obtain an antibacterial and preservative composite gel film based on purslane-derived carbon dots.
5. The preparation method according to claim 4, characterized in that: In step S22, the optimal dilution factor of the R-CDs solution is 40 times; the ratio of the volume of the polyvinyl alcohol aqueous solution, the R-CDs solution at the optimal dilution factor, acrylamide, N,N'-methylenebisacrylamide, and potassium persulfate solution is 10 mL: 5 mL: 2.0 g: 0.02 g: 1 mL; and the concentration of the potassium persulfate solution is 0.1 M.
6. The preparation method according to claim 4, characterized in that: In step S22, the optimal dilution factor for the R-CDs solution is determined as follows: After centrifugation and filtration, the R-CDs solution prepared in step S1 is diluted with anhydrous ethanol to different factors. The fluorescence emission spectrum is measured using 365 nm as the excitation wavelength. The optimal dilution factor is determined based on high fluorescence intensity, stable emission peak shape, and F... 484 / F 672 The optimal dilution factor for the R-CDs solution was determined based on a small change in the ratio; the optimal dilution factor was 40 times.
7. The preparation method according to claim 1, characterized in that, It also includes the step of coating the surface of the resulting composite gel film with a layer of glycerol.
8. An antibacterial and preservative composite gel film based on purslane-derived carbon dots, prepared by any one of claims 1-7.
9. The application of an antibacterial and preservative composite gel film based on purslane-derived carbon dots as described in claim 8 in food preservation.
10. The application according to claim 9, characterized in that: The applications include using the composite gel film as a food contact antimicrobial packaging film, preservation patch, packaging liner, or functional coating to reduce food weight loss, delay pH rise, inhibit microbial growth, and maintain sensory quality; the foods include meat, seafood, and fruits and vegetables.